Menadione-induced oxidative stress alters lipid metabolism of the mature adipocyte - Funk, Melania Iara (2020)
Obesity is closely related to metabolic disturbances, with the latter majorly caused by adipose tissue dysfunction. Oxidative stress (OS), a major characteristic of dysfunctional adipose tissue, is considered a primary contributing factor to the etiopathogenesis of obesity and associated comorbidities. However, the biochemical mechanisms by which OS alters adipocyte biology still require to be fully uncovered. We have previously demonstrated that menadione, a synthetic vitamer of vitamin K known to generate intracellular oxygen species, impairs adipogenesis by inhibiting the PI3K/Akt pathway. Our goal in this work was to study the effect of menadione-induced OS on mature adipocytes. For this purpose, differentiated 3T3-L1 adipocytes were exposed to menadione (20 and 50 µM) for 5 h, and different biochemical parameters were assessed. The exposure to menadione resulted in increased cell oxidants (65% and 122% of control, for 20 and 50 µM, respectively). However, none of the concentrations of menadione tested had any significant effect on either cell viability or morphology. The expression of adipogenic markers was evaluated by Western blot. Menadione-induced OS caused a significant decrease in the expression of PPARγ (95% and 99%, for 20 and 50 μM menadione, respectively), FAS (70% and 88%, for 20 and 50 μM menadione, respectively), C/EBPα (75% and 93%, for 20 and 50 μM menadione, respectively), and FABP4 (30% for 50 μM menadione). No changes were detected in intracellular triglyceride levels after the incubation in the presence of menadione. However, when the exposure to menadione-dependent OS was extended to 24 h, the intracellular triglyceride content was augmented by 53% and 68% upon the exposure to 20 and 50 μM menadione, respectively. At the same time, ACC (the ratelimiting enzyme in fatty acid synthesis) was activated (32% and 38% decreased phosphorylation, for 20 and 50 μM menadione, respectively). On the other hand, menadione-triggered OS also activated lipolysis (40% for 50 μM menadione). Together, our results show that OS acutely modulates both the expression and activity of different lipo/adipogenic proteins, activating fatty acids’ metabolic turnover, with enhanced lipolysis, which is overcome by fatty acid synthesis, resulting in an increased triglyceride content. Our next goal is the unraveling of the cellular signaling responsible for these metabolic changes observed.